Differences in Microbial Communities Stimulated by Malic Acid Have the Potential to Improve Nutrient Absorption and Fruit Quality of Grapes - Si, Peng; Shao, Wei; Yu, Huili; Xu, Guoyi; Du, Guoqiang (Frontiers in Microbiology, 2022)
Malic acid is a component of the rhizosphere exudate and is vital for crop growth. However, little information is available about the effects of external applications of malic acid on the nutrient absorption and quality of grape fruit, and few studies have been performed on the relationship between the changes in the rhizosphere microbial community and nutrient absorption and fruit quality of grapes after adding malic acid. 5% or 10% malic acid (the ratio of acid to the total weight of the fertilizer) combined with NPK fertilizers are represented by LM (low concentration of malic acid) and HM (high concentration of malic acid) respectively. Applying malic acid changed the grape rhizosphere microbial community structure and community-level physiological profile (CLPP) significantly, and HM had a positive effect on the utilization of substrates. The microbial community structure in the rhizosphere of the grapes with added malic acid was closely related to the CLPP. The N and P content in the leaves and fruits increased after applying malic acid compared to the control, while K content in the fruits increased significantly. In addition, malic acid significantly reduced the weight per fruit, significantly increased soluble sugar content (SSC) and vitamin C content of the fruit, and significantly improved the fruit sugar-acid ratio and grape tasting score. Moreover, the principal component analysis and grape nutrient and fruit quality scores showed that grape nutrients and fruit quality were significantly affected by malic acid and ranked as 5% malic acid > 10% malic acid > control. Pearson’s correlation heatmap of microbial composition, nutrient absorption and fruit quality of the grapes showed that the grape microbial community was closely related to grape nutrients and fruit quality. Adding malic acid was positively correlated to Planococcaceae, Bacillaceae, Woeseiaceae and Rhodobacteraceae. Furthermore, Planococcaceae, Bacillaceae, Woeseiaceae and Rhodobacteraceae were closely related to grape nutrient absorption and fruit quality. Bacillaceae and Woeseiaceae were positively correlated with TSS, while Planococcaceae and Rhodobacteraceae were positively correlated with titratable acid. Hence, Bacillaceae and Woeseiaceae were the key bacteria that played a major role in grape fruit quality and nutrient absorption after applying malic acid water-soluble fertiliser.